The Cambridge companion to Milton - Danielson, Dennis; Dobranski, Stephen B.; Brown, Cedrid; Evans, J. Martin; Burrow, Colin; Dzelzainis, Martin; Corns, Thomas N.; Hall, R. F.; Lewalski, Barbara Kiefer; Leonard, John; Carey, John; McColley, Diane K.; et al. (Cambridge [etc.] : Cambridge University Press, 1999)
Milton's social life / Stephen B. Dobranski
Milton's Ludlow masque / Cedric Brown
'Lycidas' / J. Martin Evans
'Poems 1645': the future poet / Colin Burrow
Milton's politics / Martin Dzelzainis
Milton's prose / Thomas N. Corns
Milton's sonnets and his contemporaries / R. F. Hall
The genres of 'Paradise Lost' / Barbara Kiefer Lewalski
Language and knowledge in 'Paradise Lost' / John Leonard
The Fall and Milton's theodicity / Dennis Danielson
Milton's Satan / John Carey
Milton and the sexes / Diane K. McColley
Milton and the reforming spirit / Georgia Christopher
How Milton read the Bible: the case of 'Paradise Regained' / Mary Ann Radzinowicz
Reading 'Samsom Agonistes' / Joan S. Bennett
Milton's readers / Nicholas von Maltzahn
Miltonj's place in intellectual history / William Kerrigan
Milton's works and life: select studies and resources / R. G. Siemens
Bibliografija iza pojedinih eseja
Kazalo
Keywords: Milton, John -- engleska književnost -- književna kritika